The creation : An oratorio in vocal score With a separate accompaniment for the organ or pianoforte - HAYDN, Joseph (Arthur W. Tams)
Representation of chaosnIn the beginning godnnow vanish before the holyndespairin, cursing ragenand god made the firmamem